Choosing the optimal height of a pressurized hydrocyclone for wastewater treatment of mining enterprises (Far Eastern Federal University: School of Engineering Bulletin, 2023)
The article defines the goal, which is to study the height of the hydrocyclone for the effectiveness of its work. Based on the goal, the tasks of experimental research were set to select the optimal characteristics of pressure hydrocyclones for wastewater treatment of mining enterprises. A technique for determining the disperse composition of suspended matter and modeling hydrocyclones is given. The results of experiments on the choice of the optimal diameter of the hydrocyclone, depending on its geometric and hydraulic parameters, are presented. Promising areas will be theoretical and experimental studies of hydrocyclones of various diameters with concentrated wastewater and related production tests. The article will be useful for technologists for the treatment of wastewater of coarse suspended solids and for masters and graduate students studying the issues of liquid processing and sludge dehydration in public utilities and industry.